Experimental Study on Thermal Vacuum Environment Sensitivity of Spacecraft Antenna's Typical Failure - Bi Yanqiang; Wang Jing; Qie Dianfu; Yonghong Shang; Li Xiyuan (MATEC Web of Conferences, 2017)
With the development of space applications, spacecraft antenna has become an indispensable part of any space system. The spacecraft antenna affects and constrains the performance and functionality of the entire wireless communication system as well as the entire spacecraft. Spacecraft antenna has to withstand the noise, vibration, shock and acceleration as launched, and weightlessness, high vacuum, radiation, extreme hot and cold alternating space environment on-orbit[1].The influence of different environmental factors on the typical failure modes of spacecraft antenna is different. The environmental adaptability of the spacecraft antenna depends mainly on its structural design, material, process and other factors. In this paper, the influence of different environmental factors on the typical failure modes of the spacecraft antenna is studied. The sensitivity analysis of the typical failure modes of the thermal vacuum environment is verified by experiments, which provides support for the development of the spacecraft antenna.